Petrogenesis and orthomagmatic mineral potential of the mafic-ultramafic 2.44 Ga Näränkävaara intrusion, northern Finland - Järvinen, Ville (Helsingin yliopisto, 2022)
The Paleoproterozoic Näränkävaara intrusion, northern Finland, has a surface area of 25 km × 5 km and a stratigraphic thickness of about 3 km. Based on previous and new whole-rock and mineral chemical data as well as new Sm-Nd and U-Pb isotope geochemical data, the stratigraphy, petrogenesis, and orthomagmatic mineral potential of the intrusion has been revealed. The intrusion contains a 1.5–2 km thick basal dunite series (BD) (dated in this work at 2442 ± 1 Ma) and a 1.3 km thick layered series (LS) (dated at 2436 ± 5 Ma). A 20-m-thick gabbronoritic marginal series (MS) is found between the two series, with a tectonic contact to the BD and a gradational contact to the LS. The intrusion is undeformed except for block faulting, and the rocks are mostly unaltered except for peridotitic rocks which are serpentinized. The BD is dominated by homogeneous low-porosity olivine adcumulates with <3 vol% intercumulus. Olivine orthocumulates are found at the southern basement contact (base), and heteradcumulates at the top of the series. The LS consists of a peridotitic–pyroxenitic ultramafic zone (UMZ) and a mostly gabbronoritic–dioritic mafic zone (MZ), demarcated by cumulus plagioclase in the latter. Two peridotitic reversals caused by magmatic recharge are found in the LS. Olivine orthocumulates are also found at the northern basement contact of the LS (similar to those in the BD), formed at the emplacement of the magma causing the first reversal in the LS. The olivine orthocumulates in both series display well-developed marginal reversals, and are interpreted to have crystallized relatively rapidly against cool wall rocks resulting in the trapping of an intercumulus melt component. Composition of the trapped melt has been modeled, and it is a LREE-enriched siliceous high-MgO basaltic (SHMB) magma with 13–18 wt% MgO, which is inferred as the parental magma composition of the intrusion. The melt-representative MS, and a weighted average of the LS, show a similar composition. These data from three distinct ...